Drivers and solutions to unhealthy food consumption by adolescents in urban slums, Kenya: a qualitative participatory study - Milkah N Wanjohi; Elizabeth Wambui Kimani-Murage; Michelle Holdsworth; Rebecca Pradeilles; Calistus Wilunda; Gershim Asiki; Kerstin Klipstein-Grobusch (Public Health Nutrition)
Abstract